Management of Library Facilities and Infrastructure in Increasing Students’ Interest in Reading at State Vocational High School 1 Lais Musi Banyuasin - Nurhayati, Nurhayati; Ahmad, Syarwani; Furkan, Nuril (Yayasan Sembilan Pemuda Indonesia, 2023)
This research describes how to manage the Library Sarpras in increasing students’ interest in reading. This study uses qualitative data, namely data expressed in words or symbols which are separated according to categories to draw conclusions. This research is planned to be carried out from July to November 2022. At SMK Negeri 1 Lais it is related to the problem of management of facilities and infrastructure in the library and the problem of reading interest in the library. With data collection techniques by observation, interview and documentation. The result of the research is that the management of library facilities in increasing students’ interest in reading at SMK Negeri 1 Lais Musi Banyuasin is by carrying out reading habituation program activities in the library, diligently visiting the library to read or borrow library materials.